Advances in the study of polydopamine nanotechnology in central nervous system disorders - Ren, Sijing; Xiao, Xiangyu; Lv, Jiahua; Lv, Shaomin; Wang, Xingchen; Liu, Ruihan; Kong, Qing-xia (Frontiers in Materials, 2024)
Disorders of the central nervous system (CNS) constitute a significant global health concern at the moment. Most CNS disorders are characterized by severe neuronal damage with excessive production of reactive oxygen species, which induces high levels of oxidative stress and intense inflammatory responses in the affected tissues, thus aggravating disease pathology. Notably, the blood–brain barrier makes it difficult to deliver many drugs and biologics to the CNS, which creates great difficulties in the diagnosis and treatment of CNS disorders. Recent research on polydopamine nanotechnology has led to the discovery of many promising properties; it shows strong scavenging ability for reactive oxygen species, prevents activation of pro-inflammatory microglia, and its repair function can reduce brain damage and protect neurons. Moreover, polydopamine nanotechnology can improve the blood–brain barrier permeability of biologics and reduce their neurotoxicity. It is therefore a promising candidate in the treatment of CNS disorders associated with oxidative stress. In the present paper, we review the functionality of polydopamine nanotechnology as well as the potential and recent advances of polydopamine-based nanosystems in the diagnosis and treatment of various CNS disorders, including Alzheimer’s disease, Parkinson’s disease, stroke, spinal cord injury, and glioma. Finally, we predict how polydopamine nanoparticles may guide future therapeutic strategies to address CNS disorders such as epilepsy, which currently have no cure.